Foreign Direct Investment and Export Growth: empirical evidence from Macedonian economy - Jovanka Damoska Sekuloska (Institute of Economic Research (IER), 2017)
Research background: Foreign direct investment is perceived as a valuable tool for economic growth. The growth could be realized less and more as a set of benefits depending on the FDIs features. In the period from 2009 to 2014 it is noticed a remarkable increase in the share of FDIs inflow in automotive sector in Macedonian economy, from 2.8% to 11.2%. Thus, the issue of FDIs inflow in automotive sector is a strong reason and an incentive to be examined from different aspects of influence on the economic growth. Purpose of the article: The aim of the paper is to analyze the influence of the increased FDIs inflow in automotive industry as a reason behind the remarkable export growth. The research interest of the study is to recognize the importance of the FDIs inflow structure as a determinant of the export structure. Methodology/methods:Within the paper it is developed a model that identifies the FDIs as a factor of growth of the export performances. A regression analysis is used to examine the correlation between the FDIs inflow and export. Since the correlation doesn't explain the causality, within the paper the Granger causality test is applied to examine causality between the FDIs inflow and increased export. Findings:The results suggest that FDIs create a good base for qualitative shift in the export structure of Macedonian economy. The paper associates growth of sectoral export with the growth of FDIs in that sector. Due to the increased FDI inflow in automotive industry this sector significantly has increased its share in total Macedonian export. The paperindicates that FDIs can be considered as a way of engagement in the global supplying chains which additionally influences positively to the competitiveness and export potentials of the host suppliers.
Keywords: F14; F21; F23; 330; FDI; automotive industry; export; competitiveness